Exploring COVID-19 Adaptation Strategies in Nepalese Tourism Industry: A Qualitative Study - Nepal, Bidush (Nepalese Journal of Hospitality and Tourism Management, 2023)
The tourism industry is a major part of the global economy but is also affected by crises and disasters. The COVID-19 pandemic has presented challenges for tourism and hospitality business owners in maintaining sustainability while also keeping employees safe. Despite studies on how to manage uncertainty, there is a lack of concrete examples and research on actual practices used by businesses in this sector, particularly in Nepal. This research identifies and explores the adaptations made by hospitality business owners to maintain continuity and employee safety during this uncertain time. This research, using a qualitative approach and semi-structured interviews in a conversational style with five tourism business owners in Pokhara, explores the adaptations made by these businesses to maintain continuity and employee safety during a crisis and pandemic. The paper analysed data collected from interviews through thematic analysis and used pseudonyms to protect participant anonymity. Four key adaptation strategies were identified: human resource management, reorganising operations, managing health aspects and implementing specific crisis management measures. The findings revealed that businesses were able to explore new opportunities, invest in technology, and improve efficiency. They also provided training and monitoring for sanitation and hygiene, and adapted to changes in guest and host behaviour. The paper highlights the efforts these business owners made to adapt and sustain their businesses during a difficult time.